The walking dead. The ones who live. Season 1 [videorecording (DVD)] - Gurira, Danai; Lincoln, Andrew, 1973- (AMC Studios, 2024)
The love story between Rick and Michonne. Changed by a world that is constantly changing, will they find themselves in a war against the living or will they discover that they too are The Walking Dead?